2004
DOI: 10.1071/fp03238
|View full text |Cite
|
Sign up to set email alerts
|

Gradients in stomatal conductance, xylem sap ABA and bulk leaf ABA along canes of Vitis vinifera cv. Shiraz: molecular and physiological studies investigating their source

Abstract: Gradients were observed in xylem sap ABA and in stomatal conductance along canes of Vitis vinifera L. cv. Shiraz. To investigate the source of the ABA responsible for these gradients a series of girdling and decapitation experiments were carried out. Leaf stomatal conductance and bulk ABA of leaves and apices were measured in control plants and in response to apex removal or girdling. Gradients in leaf ABA were observed over the first eight expanded leaves of field-grown Shiraz, with higher concentrations of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
74
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 46 publications
10
74
0
3
Order By: Relevance
“…In order to determine whether these stress treatments were activating ABA biosynthesis in the plant tissues, we examined the key rate-limiting steps in the plant ABA biosynthetic pathway catalyzed by ZEP and NCED (Liotenberg et al, 1999). Previous studies on grapevine leaves have showed that water stress specifically induced VvNCED1 but not VvZEP, and this is associated with an increase in bulk leaf ABA concentrations (Soar et al, 2004(Soar et al, , 2006. Our analysis shows that powdery and downy mildew infection and wounding also led to rapid and significant increases in VvNCED1 expression, but no consistent pattern in VvZEP expression was observed (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to determine whether these stress treatments were activating ABA biosynthesis in the plant tissues, we examined the key rate-limiting steps in the plant ABA biosynthetic pathway catalyzed by ZEP and NCED (Liotenberg et al, 1999). Previous studies on grapevine leaves have showed that water stress specifically induced VvNCED1 but not VvZEP, and this is associated with an increase in bulk leaf ABA concentrations (Soar et al, 2004(Soar et al, , 2006. Our analysis shows that powdery and downy mildew infection and wounding also led to rapid and significant increases in VvNCED1 expression, but no consistent pattern in VvZEP expression was observed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In grapevine, a single VvZEP gene and two VvNCED genes (VvNCED1 and -2) have been identified, but only VvNCED1 transcription appears to be linked to ABA biosynthesis in leaves under stress conditions; VvNCED2 appears to be developmentally regulated (Soar et al, 2004). Leaves infected Figure 3.…”
Section: Biotrophic Pathogen Infection and Wounding Induce The Aba Bimentioning
confidence: 99%
“…As it is well known, abscisic acid is one of the main hormonal regulators described for stomatal conductance (Lovisolo et al 2010;Pou et al 2008;Rodrigues et al 2008;Soar et al 2004;Speirs et al 2013). Also, it is the fundamental molecule behind the basis of the partial root zone drying strategy since roots under water stress produce abscisic acid and this signal is transported to leaves via xylem inhibiting stomatal conductance and growth rate.…”
Section: Effects On Plant Physiologymentioning
confidence: 99%
“…Some of the leaf ABA increase could therefore be root derived (1). The first sensing of drought typically occurs underground: roots sense a decrease in water availability, and rapidly send an ABA signal to the leaf, using the xylem as a conduit (17). However, during the fruiting stage, it is probable that the mature peanut leaves, which have more mesophyll cells and guard cells containing a lot of chloroplasts, are more sensitive to induced AhNCED1 expression and ABA biosynthesis.…”
Section: Tissue-specific Distribution Of Aba and Ahnced1 Protein In Pmentioning
confidence: 99%